Immunohistochemical Expression of LHRH Receptor in Different Compartments of Female Genital Tract in Patients With Endometrial Cancer. Issue 7 (4th August 2022) - Barczyński, Bartłomiej; Frąszczak, Karolina; Wertel, Iwona; Zakrzewska, Ewelina; Zdunek, Małgorzata; Szumiło, Justyna; Kotarski, Jan
Abstract : Luteinizing hormone–releasing hormone receptor (LHRHR) expression has been reported in various cancers, including endometrial neoplasms. Thus, LHRHR provides a potential point for therapeutic approach using LHRH analogs as carrier molecules for chemotherapeutic agents in this cancer population. However, clinical data did not prove any potential benefits for patients. We decided to assess LHRHR expression in patients with endometrial cancer to explain possible lack of efficacy in previous clinical reports. LHRHR expression was assessed immunohistochemically in different anatomic and histogenetic compartments of female genital tract of patients with endometrial cancer. The study sample consisted of paraffin tissue blocks obtained from patients who has undergone primary surgery owing to endometrial cancer. Strong LHRHR expression was found in endometrial cancer, fallopian tube, and concurrent atypical hyperplasia. Interestingly, LHRHR expression showed significant differences depending on the respective compartment of the ovary analyzed. Level of LHRHR expression in patients with primary advanced and unresectable disease, particularly in certain ovarian compartments may be substantially lower, which may influence the use of new targeted therapy regimens. The studies on secondary Müllerian system compartment and its hormonal receptor status may be crucial to understand mechanisms of lack of efficacy of LHRH hybrid molecules anti-cancer treatment.